Resolution of Multicomponent Fluorescence Emission by Phase Sensitive Detection at Multiple Modulation Frequencies - Keating-Nakamoto, Susan M. (Anal Chem, 1987)
Phase sensitive emission spectra recorded at multiple frequencies were used to determine the lifetimes and steady-state spectra of the fluorophores In two-component mixtures. This analysis does not require any previous knowledge of the lifetimes, fractional Intensities, or the emission spectra and is thus an Improvement over single frequency phase sensitive detection which requires known emission spectra or known lifetimes. Phase sensitive emission spectra are recorded at several frequencies and arbitrarily chosen detector phase angles. The data are analyzed by use of nonlinear least squares to recover the lifetimes and wavelength-dependent fractional Intensities. The latter values determine the emission spectrum and relative intensity of each component in the mixture. Using this technique, we resolved two-component mixtures of fluorescein and 9-amlnoacrldlne, 2-(p-toluidinyl)-naphthalene-6-sulfonlc acid and 6-proplonyl-2-(dlmethylamlno)naphthalene, and N-acetyl-l-tyrosinamide and N-acetyl-l-tryptophanamide. In these mixtures the lifetimes differ by about 2-fold. Analysis of simulated data is presented to Illustrate the requirements for a satisfactory resolution. For simulated two-component mixtures, the components can be resolved If the lifetimes differ by 2-fold or greater, even with extensive overlap of the emission spectra.